Implantable Cardiac Kirigami‐Inspired Lead‐Based Energy Harvester Fabricated by Enhanced Piezoelectric Composite Film. Issue 8 (12th January 2021) - Xu, Zhe; Jin, Congran; Cabe, Andrew; Escobedo, Danny; Gruslova, Aleksandra; Jenney, Scott; Closson, Andrew B.; Dong, Lin; Chen, Zi; Feldman, Marc D.; Zhang, John X. J.
Abstract: Harvesting biomechanical energy to power implantable electronics such as pacemakers has been attracting great attention in recent years because it replaces conventional batteries and provides a sustainable energy solution. However, current energy harvesting technologies that directly interact with internal organs often lack flexibility and conformability, and they usually require additional implantation surgeries that impose extra burden to patients. To address this issue, here a Kirigami inspired energy harvester, seamlessly incorporated into the pacemaker lead using piezoelectric composite films is reported, which not only possesses great flexibility but also requires no additional implantation surgeries. This lead‐based device allows for harvesting energy from the complex motion of the lead caused by the expansion‐contraction of the heart. The device's Kirigami pattern has been designed and optimized to attain greatly improved flexibility which is validated via finite element method (FEM) simulations, mechanical tensile tests, and energy output tests where the device shows a power output of 2.4 µW. Finally, an in vivo test using a porcine model reveals that the device can be implanted into the heart straightforwardly and generates voltages up to ≈0.7 V. This work offers a new strategy for designing flexible energy harvesters that power implantable electronics. Abstract : Implantable energy harvesters offer a promising solution to overcome the power challenge encountered by most biomedical devices. By prudently taking advantage of both a metamaterial and a piezoelectric composite material, a novel, flexible Kirigami‐inspired energy harvester is developed that can convert the pacemaker leads bending energy to electrical power. This technology realizes energy sustainability for implantable biomedical devices.